PERUSAHAAN YANG DINYATAKAN PAILIT (KAJIAN HUKUM PERBURUHAN) - Mayrusta Dwi Murti; Sugeng Hadi Purnomo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The problem of workers is one important thing in running a company because the company in doing activities to get a goods or services required the existence of workers, workers themselves are assets of a company. When companies experience bankruptcy the rights of workers to a company must be clear and also the process of payment of workers' wages, especially in companies that experienced bankruptcy. How legal protection is provided by the government against workers whose company is declared bankrupt. In reviewing the problem using normative juridical methods, consisting of laws, books, and journals on employment and insolvency. The results of this research is that protection starts from the rights and obligations. Workers or laborers as the implementation of development shall be guaranteed its right, regulated its obligations and developed its usefulness. Keywords: legal protection, workers, bankruptcy.